Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The current status of the servant leadership and its relationship with job satisfaction from the viewpoint of faculty members at the University of Hail Co-Prof. Miesam Fawzi Motiar Al-Azam 2. The reality of Saudi families’ support for distance education and the challenges they faced in times of disasters and crises “The Corona Virus Pandemic (COVID-19) as a Model” Prof. Wadha Habab Alotaibi 3. The Degree to Which Intermediate First-Graders in Jamoum Governorate Saudi Arabia Have Basic Skills in Mathematics Co-Prof. Abdul Malik Misfer Al-Maliki, Mr. Othman Abdullah Al-Sulami 4. The competencies of social and emotional learning and their relationship to future skills among mathematics teachers in North Sharqiyah Governorate, Sultanate of Oman from their point of view Dr. Ali Said Sulaiyam Al-Matari, Mrs. Shamsa Mohamed Rashid Al-Noumani 5. Academic buoyancy among female students of Umm Al-Qura University, Al-Zahir Branch Mrs. Tahany Amaanullah Qasim 6. The effect of using language learning strategies in teaching Arabic on the development of Some language skills of primary school students Prof. Mahmoud Helal Abdelkader 7. The reality of employing the Internet of Things in the educational process from the point of view of faculty members in Saudi universities Mrs. Sarah Fahad Alharbi , Prof. Eiad Abdul-Aziz Altaf